Interference cancellation with combined pre-distortion filtering and transmit diversity - Correia, Américo (2003)
It is intended to specify the pre-distortion (PD) filtering technique, which can be used to combat the Multiple Access Interference (MAI), combined with a variation of the Selective Transmit Diversity (STD) for high data rate transmissions over frequency selective Rayleigh fading channels. By pre-distorting the signals to be transmitted by the Base Station (BS) with a Minimum Variance (MV) algorithm, the orthogonality between the desired signal and all interfering signals can be improved. We combine the PD with a variation of the conventional STD, which is optimized for the proposed pre-distortion scheme, allowing an increase in the reduction of MAI and combating the fading. Both schemes are closed loop systems with Feedback Indication (FBI). The increase in performance is achieved with an increase in power processing in the BS, avoiding any need to increase complexity in the Mobile Station (MS).